(847) Product Performance Model PPM نموذج أداء المنتج - Al Shafei, Al Walid (The Institute of National Planning, 2024)
The last two decades have witnessed the development of a branch of economic theory concerning the "Theory of Economic Development." Consequently, the volume of literature in this area has rapidly expanded. Much of the early work focused on attempts to define and measure economic development, highlighting the drawbacks of alternative definitions and measures. A standard textbook today devotes its first chapter to discussing alternative measures, concluding that Gross National Product (GNP), Net National Product (NNP), or per capita income can serve as measures of material welfare, with warnings about intertemporal and inter-country comparison difficulties.